LINC01492 is associated with susceptibility to large atherosclerotic stroke and levels of inflammatory factors - Jianyu Liu; Da Liu; Xing Guo; Li Zhou; Zhiyao Xu; Hua Liu (Brain Circulation)
BACKGROUND: LINC01492 polymorphism has been implicated in the susceptibility of large artery atherosclerotic (LAA) stroke; however, a dearth of systematic research exists regarding this association in the Asian population at present. SUBJECTS AND METHODS: This study enrolled Han Chinese patients with LAA stroke (n = 428) and age- and sex-matched controls (n = 434). We employed dominant, recessive, and codominant genetic models to analyze the distribution of alleles and genotypes for 14 tag single nucleotide polymorphisms (SNPs) in LINC01492. Furthermore, we quantified the transcript levels of LINC01492 as well as concentrations of inflammatory factors (interleukin [IL]-1β, IL-6, IL-8, IL-10, IL-18, tumor necrosis factor alpha, and CCL18). In addition, we explored the association between these SNPs and levels of inflammatory factors. RESULTS: The rs10990654 AA genotype of LINC01492 was markedly associated with a heightened risk of LAA stroke (odds ratio [OR] = 6.403, 95% confidence interval [CI] = 1.180–34.734, P = 0.031). Conversely, both the GG genotype of rs10990654 (OR = 0.614, 95% CI = 0.384–0.980, P = 0.041) and the GG genotype of rs16922693 (OR = 0.518, 95% CI = 0.313–0.857, P = 0.010) were identified as being linked to a reduced risk in this study population. In addition, the transcription level of LINC01492 was markedly reduced in patients compared to controls. Furthermore, significant variations were observed in IL-10 and IL-18 levels across genotypes at LINC01492 polymorphism loci among patients. CONCLUSIONS: The genetic polymorphisms and transcript levels of LINC01492 exhibit an association with susceptibility to LAA stroke, and the available evidence suggests that this association may be mediated through IL-10 and IL-18. TRIAL REGISTRATION: The trial was registered with the Chinese Clinical Trial Registry (www.chictr.org.cn) under trial registration number ChiCTR2000032684.